Synthetic peptides designed to modulate adiponectin assembly improve obesity‐related metabolic disorders. (2nd November 2017) - Hampe, Lutz; Xu, Cheng; Harris, Paul W R; Chen, Jie; Liu, Ming; Middleditch, Martin; Radjainia, Mazdak; Wang, Yu; Mitra, Alok K
Abstract : Background and Purpose: Adiponectin, an adipokine possessing profound insulin‐sensitizing and anti‐inflammatory properties, is a potent biotherapeutic agent . The trimeric adiponectin subunit assembles into hexameric and functionally important higher molecular weight (HMW) forms, controlled by the endoplasmic reticulum protein 44 (ERp44). Obesity‐induced ER stress decreases the HMW form in serum, contributing to the development of insulin resistance and Type 2 diabetes. In this study, a panel of synthetic peptides, designed to target ERp44–adiponectin interactions, were tested for their effects on circulating levels of HMW adiponectin. Experimental Approach: Peptides derived from the ERp44 binding region of adiponectin and immunoglobulin IgM were synthesized with or without a cell‐penetrating sequence. Cultures of 3T3‐L1 adipocytes were incubated with the peptides for assessing the assembly and secretion of HMW adiponectin. Mice given standard chow or a high‐fat diet were treated acutely or chronically, with the peptides to investigate the therapeutic effects on insulin sensitivity and energy metabolism. Results: The designed peptides interfered with ERp44–adiponectin interactions and modulated adiponectin assembly and release from adipocytes. In particular, IgM‐derived peptides facilitated the release of endogenous adiponectin (especially the HMW form) from adipose tissue, enhanced its circulating level and the ratio of HMW‐to‐total‐adiponectin in obese mice. Long‐term treatment of mice fed with high‐fat diet by IgM‐derived peptides reduced the circulating lipid levels and improved insulin sensitivity. Conclusions and Implications: Targeting ERp44–adiponectin interactions with short peptides represents an effective strategy to treat of obesity‐related metabolic disorders, such as insulin resistance and Type 2 diabetes.